Baricitinib Improves Bone Properties and Biomechanics in Patients With Rheumatoid Arthritis: Results of the Prospective Interventional BARE BONE Trial - Simon, David; Minopoulou, Ioanna; Kemenes, Stephan; Bayat, Sara; Tascilar, Koray; Mutlu, Melek Yalcin; Valor-Méndez, Larissa; Krönke, Gerhard; Hueber, Axel J.; Schett, Georg; Kleyer, Arnd (Arthritis and Rheumatology, 2023)
Objective: Rheumatoid arthritis (RA) is characterized by erosive joint damage, deterioration of bone mass, and biomechanics. Preclinical evidence suggests a beneficial effect of Janus kinase inhibition (JAKi) on bone properties, but clinical data are scarce to date. In this study, we evaluated the effect of JAKi through baricitinib (BARI) on 1) volumetric bone mineral density (vBMD), bone microstructure, biomechanics, and erosion repair and 2) synovial inflammation in RA patients. Methods: Prospective, single-arm, interventional, open-label, single-center phase 4 study in RA patients with pathological bone status and clinical indication of JAKi (BARE BONE trial). Participants received BARI (4 mg/day) over 52 weeks. To assess bone properties and synovial inflammation, high-resolution computed tomography scans and magnetic resonance imaging were performed at baseline (BL), week 24, and week 52. Clinical response and safety were monitored. Results: Thirty RA patients were included. BARI significantly improved disease activity (Disease Activity Score in 28 joints using the erythrocyte sedimentation rate: 4.82 ± 0.90 to 2.71 ± 0.83) and synovial inflammation (RAMRIS synovitis score: 5.3 [4.2] to 2.7 [3.5]). We observed a significant improvement in trabecular vBMD with a mean change of 6.11 mgHA/mm3 (95% confidence interval [95% CI] 0.01–12.26). Biomechanical properties also improved with mean change from baseline in estimated stiffness of 2.28 kN/mm (95% CI 0.30–4.25) and estimated failure load of 98.8 N (95% CI 15.9–181.7). The number and size of erosions in the metacarpal joints remained stable. No new safety signals with BARI treatment were observed. Conclusion: Bones of RA patients improve with BARI therapy, as shown by an increase in trabecular bone mass and an improvement of biomechanical properties.
CRIS-Team Scopus Importer:2023-09-29